Islam and Local Wisdom of Malay Society in Maintaining the Harmony Between Religious and Cultural Plurality (a Case Study of Batubara’s Malay Society) - Muhammad Qorib (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Islam came to the earth to bring the missions of the divinity (ilahiyah) and the humanity (insaniyah). The universal values ​​in Islam are very important to be implanted as a view of life in order to summon human values ​​in social life. Therefore, the foundation of ethics such as the concept of al-’adalah (justice), al-hurriyyah (independence), as-shura (democracy), al–musawah (equality), al–ukhuwwah (brotherhood), and at-tasamuh (tolerance), are very important to be more appreciated widely. By an approach to perfect the morals of mankind, without eliminating the previous tradition and even able to accommodate local culture, that’s the value which the Prophet had as his view of life when developing the precepts of humanity and mankind in Arab society at that time. Therefore, the researchers concluded that the research about the local wisdom of Batubara’s Malay culture in Tanjung Tiram district is a miniature that can be applied in other communities, because Batubara’s Malay can accommodate the Prophet’s view. This study has revealed how the implementation of cultural values ​​can coexist with Islamic values ‘​​rahmatan lil alamin’ and integrate Islamic values ​​in the local wisdom of the inhabitant’s culture by using descriptive qualitative method in which the researchers were involved actively in meeting the participants, environments and institutions related to the research in natural situations. The researchers also conducted interviews with informen in order to reveal the application of Islamic values ​​in the culture of the Malay community in maintaining harmony between religious and cultural plurality. The local wisdom such as the value of tolerance in rhymes, justice, freedom, democracy, and tolerance on the leadership of lima laras kingdom, the value of respect on the traditional Malay dances, the value of patience, precision, beauty in the weaving process of Batubara’s traditional cloth (songket) are capable of being a symbol of harmony between religious and cultural plurality in Tanjung Tiram district, Batubara Regency. Keywords : Islam , local wisdom , Malay culture Batubara, harmony